ПРОБЛЕМЫ СОХРАНЕНИЯ БИОРАЗНООБРАЗИЯ ИХТИОФАУНЫ И ВОЗМОЖНЫЕ ПУТИ ИХ РЕШЕНИЯ (Eurasian Journal of Ecology, 2016)
In given article problems ofpreservation of a biodiversity of a fish fauna are designated, security actions are analysed and the complex of necessary measures for preservation rare and vanishing species offishes is resulted.